2011
DOI: 10.1590/s1415-43662011000100007
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da salinidade no desenvolvimento e crescimento de mudas de carnaúba (Copernicia prunifera (Miller) H.E.Moore)

Abstract: Identificar o impacto da salinidade no desenvolvimento e crescimento de espécies resistentes a altas concentrações salinas é de fundamental importância para a recuperação de áreas salinizadas do semiárido nordestino brasileiro. Visando contribuir para a resolução desta problemática, o presente trabalho avaliou o efeito de diferentes níveis de salinidade para o desenvolvimento e o crescimento da carnaúba, espécie nativa e de extremo valor econômico para a região. Os níveis analisados foram: 0, 25, 50, 100 mM de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
7
1
5
Order By: Relevance
“…The tolerance limit is an excellent primary bioindicator of soils with high saline concentrations that change according to variations in the environment. This value is higher than that found by Holanda et al (2011), who studied the same species subjected to saline stress and demonstrated that the development of the carnauba was compromised in concentrations greater than or equal to 3 dS m -1 . These authors studied the carnauba for up to 120 days after sowing.…”
Section: Nutrient Composition Of Carnauba Plants Under the Effects Ofcontrasting
confidence: 58%
“…The tolerance limit is an excellent primary bioindicator of soils with high saline concentrations that change according to variations in the environment. This value is higher than that found by Holanda et al (2011), who studied the same species subjected to saline stress and demonstrated that the development of the carnauba was compromised in concentrations greater than or equal to 3 dS m -1 . These authors studied the carnauba for up to 120 days after sowing.…”
Section: Nutrient Composition Of Carnauba Plants Under the Effects Ofcontrasting
confidence: 58%
“…Segundo D'Alva (2004), a C. prunifera tem distribuição geográfi ca nos vales dos rios nordestinos, especialmente no meio-norte e nas maiores latitudes do sertão. A espécie ocorre em ambientes com solos argilosos e em aluviões, onde há maior saturação hídrica e elevados teores de salinidade (HOLANDA et al, 2011). Estas áreas podem permanecer inundadas por alguns meses do ano e, posteriormente, chegam a ser submetidas ao estresse hídrico nos períodos mais secos.…”
Section: Dados Etnoecológicosunclassified
“…In this framework, the carnaubeira (C. prunifera (Miller) HE Moore), an endemic palm of the semi-arid Northeast belonging to the Arecaceae Family, has been used historically by people from the northeast region of Brazil as a source of income due to its economic and cultural importance. The extraction of the ceriferous powder from its leaves is an extractive activity responsible for the sustenance of several families during the drought period, which extends from July to December [19][20][21].…”
Section: Introductionmentioning
confidence: 99%